Pengaruh Tayangan Native Speakers Without Substitles Terhadap English Lingua Franca Di Kalangan Young Learners - Yovita Mumpuni Hartarini; Frida Widyawati Triasningrum (CV. ULIL ALBAB CORP, 2022)
This study reveals one way to introduce English as a universal language from an early age to children at home by subscribing to Digital TV. If subtitles are not used, the viewers then try to listen to the meaning of the speakers of the characters, which in this case are called native speakers. This is what is called listening, which is the main basic ability and skill in language. As elementary school students as well as young learners, English is still an interesting subject for them because they are considered as intelligent people if they can speak English well. Although the English course is not tested in the UN (National Examination) at the elementary level, they will find the next level of education when they face the UN. Thus, it is necessary to have ways and strategies in mastering English at least to be trained in listening to films on Digital TV shows without subtitles. The research team has found several elementary school students who excel in their English subject because their parents subscribe to digital TV at home and there is an assumption from parents that when their children's favorite cartoon films that are still in elementary school have been watched without subtitles, they are able to increase their vocabulary (vocabularies) and daily verbal utterances interspersed with English (lingua franca) which they apparently got from Digital TV shows at home.